2005
DOI: 10.2224/sbp.2005.33.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Team Composition and Learning Behaviors in Cross-Functional Teams

Abstract: In this study we examined the effects of 2 types of team diversity (functional and positional diversity) and team learning behaviors on the performance of cross-functional teams. Enterprise resource planning system implementation teams were selected for investigation because of their cross-functional characteristics. The study results indicate that team learning behaviors had a significant and consistently positive effect on team performance. Functional diversity had a negative effect on team satisfaction, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
1
15
0
5
Order By: Relevance
“…However, only a small number of project team studies examined the relationship between learning activities and the outcomes studied in this paper. While no studies which analyze the effect of learning activities on efficiency were found, learning activities were found to have a significant and positive effect on effectiveness (Yeh and Chou, 2005) but no significant association with innovation (Heinz et al, 2006). Thus, the hypotheses developed are:…”
Section: Key Process Factorsmentioning
confidence: 96%
“…However, only a small number of project team studies examined the relationship between learning activities and the outcomes studied in this paper. While no studies which analyze the effect of learning activities on efficiency were found, learning activities were found to have a significant and positive effect on effectiveness (Yeh and Chou, 2005) but no significant association with innovation (Heinz et al, 2006). Thus, the hypotheses developed are:…”
Section: Key Process Factorsmentioning
confidence: 96%
“…According to recent studies (Foldy, 2003; Yeh and Chou, 2005), the path from diversity to performance can best be described as a learning process. Group learning behaviour can be outlined as activities by which individuals seek to acquire, share, refine, or combine task‐relevant information through mutual interaction (Argote, 1999).…”
Section: Hypothesesmentioning
confidence: 99%
“…11 Others argue that organisational position and status diversity may at times play a positive role in team performance but that disciplinary diversity is more likely to have a consistently negative effect. 12 Although the negative effects of disciplinary diversity can often be mitigated by learning behaviours (such as seeking feedback, asking for help, and talking about errors), similar to the demographic diversity domain, such behaviours take time, which is becoming less of an option in today ' s fast-moving environments. 13 Despite a rich history of studies examining the relationship between surface diversity and team performance, historical fi ndings are mixed.…”
Section: Diversity and Team Performancementioning
confidence: 99%